2007
DOI: 10.1063/1.2757149
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of biaxial stress and its effect on optical properties of ZnO thin films

Abstract: Biaxial stress of ZnO film deposited on quartz was measured by side-inclination x-ray diffraction technique, indicating that the film is subjected to a tensile stress. One part of the stress is induced by thermal mismatch between the ZnO and the quartz and increases with annealing temperature, while another part results from lattice mismatch and is about 1.03GPa. The optical band gap of the ZnO film shows a blueshift with increasing biaxial tensile stress, opposed to the change of the band gap with biaxial ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(47 citation statements)
references
References 11 publications
1
44
1
Order By: Relevance
“…For p-type samples at P O2 Z0.75, the c-axis lattice constants are much larger than the value of 0.5203 nm of undoped ZnO. It has been reported that ZnO film grown on quartz is subjected to biaxial tensile stress due to large thermal mismatch between film and substrate, which result in decrease of the lattice constant c of the films [17]. Thus, the increase of the c-axis lattice constant cannot stem from stress but substitution of some Ag for Zn in the films due to the larger ionic radius of Ag + (1.26Å) than that of Zn 2 + (0.74Å) [18,19].…”
Section: Resultsmentioning
confidence: 94%
“…For p-type samples at P O2 Z0.75, the c-axis lattice constants are much larger than the value of 0.5203 nm of undoped ZnO. It has been reported that ZnO film grown on quartz is subjected to biaxial tensile stress due to large thermal mismatch between film and substrate, which result in decrease of the lattice constant c of the films [17]. Thus, the increase of the c-axis lattice constant cannot stem from stress but substitution of some Ag for Zn in the films due to the larger ionic radius of Ag + (1.26Å) than that of Zn 2 + (0.74Å) [18,19].…”
Section: Resultsmentioning
confidence: 94%
“…When the ZnO film is fabricated at nonstoichiometric ratio, there exist excessive zinc or oxygen atoms in the ZnO film. A previous literature [15] indicates that the excessive Zn or O driven by the biaxial stress can move to the surface and produce a lot of defects at the surface, leading to the formation of rough surface with reticulated structures. However, when the ZnO Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The measured residual stresses were along the laser scanning direction, and the selected entrance angle of X-ray was 0 • , 21.3 • , 30.9 • and 39 • , respectively. The residual stresses ( ) were calculated by the following equation [21]:…”
Section: Experimental Methodsmentioning
confidence: 99%